Analysis of input coupler asymmetry influence on particle beams dynamics in accelerators with superconducting cavities - Gusarova, M.A.; Zavadtsev, A.A.; Krasnov, A.A.; Makarov, V.A.; Sobenin, N.P.; Shvedunov, V.I. (Вопросы атомной науки и техники, 2008)
An investigation of input coupler asymmetry influence on electron beam’s dynamics in energy recovery linacs (ERL) with superconducting cavities was carried out. Were considered several types of input power couplers – coaxial and waveguide, asymmetric and symmetric. Based on numerical modeling electromagnetic fields distribution in accelerating cavity with input coupler was found, the transverse deflecting impulse was calculated. Проведено дослідження впливу асиметрії вводу потужності в надпровідні резонатори інжекційної частини прискорювача з рекуперацією енергії (ERL) на динаміку пучків електронів. Розглянуто коаксіальні і хвилеводні, асиметричні і симетричні варіанти вводу потужності. На основі чисельного моделювання знайдено розподіл електромагнітних полів у прискорювальному резонаторі з пристроєм вводу потужності, розраховано величину поперечного відхиляючого імпульсу. Проведено исследование влияния асимметрии вводов мощности в сверхпроводящие резонаторы инжекционной части ускорителя с рекуперацией энергии (ERL) на динамику пучков электронов. Рассмотрены коаксиальные и волноводные, асимметричные и симметричные варианты вводов мощности. На основе численного моделирования найдено распределение электромагнитных полей в ускоряющем резонаторе с устройством ввода мощности, рассчитана величина поперечного отклоняющего импульса.